A color-related bias in offside judgments in professional soccer: A matter of figure-background contrast? - Wühr, P.; Memmert, D. (PLOS ONE, 2023)
We investigated the impact of outfit colors on the frequency of offside judgments in soccer. In a recent laboratory study, observers made more offside judgments against forwards wearing the outfit of Schalke 04 (blue shirts, white shorts) than against forwards wearing the outfit of Borussia Dortmund (yellow shirts, black shorts), when figure-background luminance contrast was higher for the former team. Here, we investigated whether a similar effect is present in real matches of the German Bundesliga. Study 1 revealed a higher offside score for Schalke 04 than for Borussia Dortmund in matches between these clubs. Studies 2-4 showed higher offside scores for teams wearing a blue/white outfit, and lower offside scores for teams wearing a yellow/black outfit, in their matches against all other Bundesliga teams. Together, results suggest that more offside judgments are made against teams of higher salience, possibly induced by differences in figure-background contrast. Notably, this color-related bias occurred in our study even though a Video-Assistant Referee (VAR) supervised the (offside) decisions of the Assistant Referees.